The Impact of Education during the Covid-19 Period in Indonesia - Redyanto Sidi (Journal of Elementary School Education, 2022)
This study aims to understand the impact of the Covid-19 pandemic on teaching teachers and students. This research also hopes to understand the impact of the Covid-19 pandemic on the learning process of teachers, students and parents, as well as the obstacles faced by teachers in teaching. In addition, the authors also review several policies that have been implemented by the government of the Republic of Indonesia and also see the positive aspects of the Covid-19 pandemic in the teaching process of teachers and students. This research method uses a qualitative case study, which is used to obtain information about the problems raised by the author. The resource persons needed for this research are students, teachers and parents. The results showed that Covid-19 had a major impact on all parties (teachers, students and parents). Lack of knowledge about the use of technology and huge expenditures hinder the learning process.